Regulasi dan Manajemen Risiko Layanan Fintech Peer-To-Peer Lending di Indonesia: Penelitian Pusaka Aspek Hukum dan Perbankan - Nur Sakbaniah; Nur Melviyani; Fikri Haikal Adha; Zulia Agustina (Media Hukum Indonesia (MHI), 2026)
The development of financial technology peer-to-peer (P2P) lending has revolutionized financial inclusion but faces complex systemic risks in Indonesia. This study analyzes the urgency of regulation and risk management in the online lending ecosystem through a juridical-normative approach. As a financial service connecting lenders and borrowers digitally, P2P Lending demands rigorous oversight to mitigate defaults and protect consumers. Data indicates that while loan disbursements have reached significant figures, fluctuations in the 90-day default rate (TWP90) and the proliferation of illegal entities remain critical issues threatening financial stability. Employing a qualitative library research method, this study examines positive legal instruments, including the P2SK Law and sharia-compliant governance, to address existing regulatory gaps. The results demonstrate that conventional risk mitigation is insufficient without the integration of transparent credit scoring algorithms and massive cross-institutional collaboration. The study concludes that a transformation toward a preventive-predictive oversight model is imperative to ensure industry sustainability. Therefore, policy synchronization between financial authorities and law enforcement is essential to create a digital financing ecosystem that is inclusive, equitable, and resilient to future governance threats.